Penerapan Mobilisasi Dini terhadap Proses Penyembuhan Luka pada Pasien Post Sectio Caesarea - Wiwik Norlita; Isnaniar; Rahmi, Amini; Novi Anggela Pitri (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2025)
Cesarean section (CS) is a common surgical procedure performed to save the lives of both mother and baby. However, this operation leaves a wound that requires optimal healing. Early mobilization is believed to accelerate wound healing by increasing blood circulation and preventing postoperative complications. Objective: To determine the effect of early mobilization on the wound healing process in post-cesarean section patients. Method: This study used a descriptive case study approach involving two post- CS mothers at Arifin Achmad General Hospital in Pekanbaru. Early mobilization intervention was carried out over three days, and wound healing was assessed using the REEDA scale. Results: Both respondents showed good wound healing outcomes, with REEDA scores of 2 and 4 on the third postoperative day. No additional complications were observed during the intervention period. Conclusion: Early mobilization is effective in accelerating wound healing in post-cesarean section patients and can be recommended as part of standard postoperative care.